2008
DOI: 10.1002/da.20425
|View full text |Cite
|
Sign up to set email alerts
|

Differential familial liability of panic disorder and agoraphobia

Abstract: To examine the familial liability of panic disorder (PD) and agoraphobia (AG) in a community sample, namely the effect of parental PD and AG on the offspring's risk to develop either or both conditions in adolescence or adulthood. A representative community sample of N=3,021 adolescents and young adults aged 14-24 years at baseline was followed up over a period of 10 years in up to four waves. Family information was assessed by either direct interviews with at least one parent or by using subjects' family hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 70 publications
(76 reference statements)
3
29
1
Order By: Relevance
“…According to our results there were also significant associations between agoraphobia and PROGINS Alu polymorphism of the progesterone receptor gene. This finding is in line with the previous studies which found a familial liability of PD and agoraphobia whereas Nocon et al (27), suggested that agoraphobia might enhance familial transmission of PD. According to our results it seems that T1 allele increases the risk of agoraphobia.…”
Section: Discussionsupporting
confidence: 93%
“…According to our results there were also significant associations between agoraphobia and PROGINS Alu polymorphism of the progesterone receptor gene. This finding is in line with the previous studies which found a familial liability of PD and agoraphobia whereas Nocon et al (27), suggested that agoraphobia might enhance familial transmission of PD. According to our results it seems that T1 allele increases the risk of agoraphobia.…”
Section: Discussionsupporting
confidence: 93%
“…The few available studies in this area generally document associations in juveniles that are comparable to those found in adults. [136][137][138][139] Thus, research on the clinical expression of PAs or PD in children and adolescents does not support the inclusion of any age-specific criteria when considering the diagnosis.…”
Section: Clinical Expressionmentioning
confidence: 99%
“…Family studies can provide insight into the shared aetiology of disorders and the availability of different types of family relationships allows dissection into relative contributions of shared genetic and environmental causes. Clinical and non-clinical family studies reveal evidence for familial aggregation in the aetiology of depression[20;21], SP[20;22;23], PD[22;2427], and AG[23;24;2628]. Twin studies also suggest that genetic influences play a significant role in the familial aggregation of depression and anxiety disorders[29–35].…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that AG without a history of PD is part of a panic disorder syndrome[10] and has been shown to be predictive of onset of PD in a longitudinal study[51]. However, Wittchen et al[24] have argued that AG exists as a clinically significant phobic condition independent of PD[8]. Evidence for a common genetic aetiology of AG without PD and PD would provide support for AG being part of a PD syndrome, but few family studies have been published and their interpretation is limited by small sample size, clinical setting and historical nosology [24].…”
Section: Introductionmentioning
confidence: 99%